Covid-19 in children- An envolving picture - Arruvito, Maria Lourdes (2021)
Among the most intriguing observations in Coronavirus disease 2019 (COVID-19) is the reduced incidence and mortality in children. In fact, and in contrast to other viral respiratory infections such as those caused by influenza and respiratory syncytial virus, SARS-CoV-2 infection usually develop a mild course in children. The reasons for this remain unclear. Considering that pulmonary infiltration by neutrophils plays a relevant role in the development of severe COVID-19 in adults, we analyzed whether neutrophils in children infected with SARS-CoV-2 expressed a particular phenotypic profile. We found that neutrophils from children with COVID-19 express a distinct signature characterized by a reduced expression of adhesion molecules involved in neutrophil migration together with an increased expression of both, the inflammatory markers CD64, HLA-DR and PECAM-1 and the inhibitory receptors leukocyte-associated immunoglobulin-like receptor 1 (LAIR-1) and programmed death-ligand 1 (PD-L1). This finding is unusual as neutrophil activation is associated with the up-regulation of adhesion molecules as it was observed in adult COVID-19. We hypothesized that this particular signature might prevent neutrophil infiltration in the pulmonary capillaries thus providing protection against tissue injury in the children.While the course of SARS-CoV-2 infection in children is usually mild, some children develop severe COVID-19. It has been shown that severe disease in adults is associated with a delayed kinetic of antibody production. We also studied whether a defective antibody response could be associated with a more severe condition in children. We found that children with severe COVID-19 display a very poor and late antibody response against SARS-CoV-2. This weak antibody response was associated with a low frequency of circulating Follicular Helper T cells and a systemic inflammatory response revealed by high levels of inflammatory cytokines in plasma. Vaccines against COVID-19 have shown very high levels of safety and effectiveness. In countries that have led vaccination globally, such as Israel and the United Kingdom, the pandemic seems to hold first in the infection of children. In this scenario, it is urgent to characterize the factors determining the predisposition of some children to suffer severe COVID-19.